PERAN GURU AKIDAH AKHLAK SEBAGAI UPAYA PENINGKATAN AKHLAK SISWA - Zahiq, Moh (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Education in the increasingly developing globalization era has many positive and negative impacts on people's lives, we are faced with quite serious moral and moral problems, we must be good at processing education in the globalization era, both within the family, community, education and the State. Teachers have an important role in the formation of morals. Mainly a teacher of morals. This study aims to explore the role of the moral creed teacher as an effort to improve morals. The research uses literature research methods, with documentary data collection methods. And with a content analysis model. The results of the study show that student morals can be formed when the teacher applies all of his roles, namely: The teacher as educator, mentor, teacher, role model, adviser, facilitator, motivator, evaluator and innovator